Taman Bumi Mengkarang Universitas Jambi sebagai Media Pembelajaran di Teknik Kebumian - Hari Wiki Utama; Maryadi Maryadi; Edi Sutrisno; Arliyusmar Arliyusmar; Erik Saputra (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2023)
IN THE 4.0 ERA, ALMOST EVERY ACTÄ°VÄ°TY RELATED TO THE EARTH REQUÄ°RES Ä°NTEGRATED AND SUSTAÄ°NABLE GEOLOGÄ°CAL DATA AND CONCEPTS.Â These activities include exploration and exploitation of geological resources. Earth Engineering students are led to be able to understand all types of rocks as the basis of earth science. Rock outcrops are clear and can be seen in real terms in the field. Therefore, the condition is quite far from campus, causing an effective learning media for prospective Bachelor of Earth Engineering students to recognize rocks. With the establishment of this Karang-Earth Park, it can be the right solution for this problem. The existence of this geopark miniature will later be taken from the rock outcrops in the Merangin-Jambi UNESCO Global Geopark Territory. This area was chosen for display rocks, because it is very complete of all types of rocks that are unique in terms of the age of the rocks, which were 323 Ma Carbon to Quaternary age.